Pemanfaatan Pupuk Organik Padat untuk Meningkatkan Pertumbuhan Kangkung Darat (Ipomoea reptans poir.) secara Organik - Ratna Widya Rakhmawati; Choirul Anam; Dian Eka Kusumawati (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2025)
Ipomoea reptans Poir. Or often known as land kale is one kind of seasonal vegetable that people eat a lot of because it tastes so good, is easy to cultivate, and has economic value. However, if inorganic fertilizers are used continuously during the production process, they can disrupt the ecosystem and soil quality The objective of this study was to investigate how different solid organic fertilizers affect the development and yield of landraces. One of the components, the type of solid organic fertilizer, with seven levels, was put into a Randomized Block Design (RAK). The Least Significant Difference (BNT) test was performed at 5% if the data were analyzed using analysis of variance (ANOVA) and significant differences were identified. The results showed that, when compared to other forms of organic fertilizer, the use of bat droppings (guano) produced the best effect on the development and yield of land kale plants. Thus, guano fertilizer has the potential to be an alternative to inorganic fertilizers in the cultivation of land kale organically and environmentally friendly.